LEGAL EFFORT AGAINST PERFORMERS AND VICTIMS OF VIOLENCE OF BULLYING IN INDONESIA (ANALYSIS OF LAW NUMBER 35 YEAR 2014) - M. Iqbal; Uswah Hasanah (Proceeding International Seminar of Islamic Studies, 2022)
Bullying is a phenomen on that is already familiar in Indonesia and abroad. This often happens in elementary to upper level schools, even at the university level. This study aims to examine further about acts of bullying that have a negative impact on both perpetrators and victims based on the existing law in Indonesia, namely the Child Protection Law No. 35 of 2014. This research method is descriptive, using normative juridical law research methods. The results of this study indicate that in Indonesia itself there are regulations regarding the crime of bullying, namely Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. In Article 76C which provides protection that leads to physical violence, but violence is not only physical but there is non-physical violence, and acts of bullying are non-physical acts of violence but can have a lifelong psychological trauma for the victims, as well as rules for sanctions. punishment given.Keywords:Legal Protection Efforts, Bullying Violence